A glyoxal-specific aldehyde signaling axis in Pseudomonas aeruginosa that influences quorum sensing and infection - Christopher J. Corcoran; Bonnie J. Cuthbert; David G. Glanville; Mailyn Terrado; Diana Valverde Mendez; Benjamin P. Bratton; Daniel E. Schemenauer; Valerie L. Tokars; Thomas G. Martin; Lawrence W. Rasmussen; Matthew C. Madison; Andrew F. Maule; et al. (Nature Communications)
Abstract The universally conserved α-oxoaldehydes glyoxal (GO) and methylglyoxal (MGO) are toxic metabolic byproducts whose accumulation can lead to cell death. In the absence of a known, natural inducer of the GO-specific response in prokaryotes, we exploited RNA-seq to define a GO response in the bacterial pathogen Pseudomonas aeruginosa. The highest upregulated operon consisted of the known glyoxalase (gloA2) and an antibiotic monooxygenase (ABM) domain of unknown function - renamed here Aldehyde responsive quorum-sensing Inhibitor (ArqI). The arqI-gloA2 operon is highly specific to GO induction and ArqI protein responds by migrating to the flagellar pole. An ArqI atomic structure revealed several unique features to the ABM family, including a ‘pinwheel’ hexamer harboring a GO-derived post-translational modification on a conserved arginine residue (Arg49). Induction of ArqI abrogates production of the Pseudomonas Quinolone Signal (PQS) quorum sensing molecule and was found to directly interact with PqsA; the first enzyme in the PQS biosynthesis pathway. Finally, we use a sepsis model of infection to reveal a survival requirement for arqI-gloA2 in blood-rich organs (heart, spleen, liver and lung). Here we define a global GO response in a pathogen, identify and characterize the first GO-specific operon and implicate its role in PQS production and host survival.